HOW THE IMPLEMENTATION OF SCIENCE AND TECHNOLOGY TRANSFORMATION IN DEVELOPING POTENTIAL OF HIJAB SMEs IN GRESIK - Jun Surjanti; Yoyok Soesatyo; Sanaji Sanaji; Setya Chendra Wibawa (Proceedings on Engineering Sciences, 2019)
Hijab SMEs is one of the small enterprises driving the economy of Gresik. However, in its growth, they have not yet reached a significant target. This condition is due to lack awareness of SMEs actors in implementing science and technology transformation to manage and develop their businesses as causing less optimal of the business potentials. This study aims to discover how science and technology transformation is implemented by Hijab SMEs in Gresik. This study applied explanatory qualitative approach and employed 7 hijab craftsmen as respondents. Data were collected through questionnaires and observations. The data were analyzed using Miles and Huberman techniques. The study found that only one of seven respondents well implemented science and technology transformation proved by marked as good in all aspects assessed (production, marketing, productivity, and networking). Further research is needed especially in employing appropriate methods to introduce science and technology transformation to Hijab SMEs actors.